Comparative Analysis of Indonesian Bank Health Using Risk, Governance, Earnings, and Capital Approach - Nursasi, Enggar (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze and compare the health level of State-Owned Banks and National Private Banks in Indonesia based on the Risk-Based Bank Rating (RBBR) approach which includes four main components, namely Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital (RGEC). This research uses secondary data in the form of annual financial statements of banks listed on the Indonesia Stock Exchange (IDX) during the 2020–2022 period. Each aspect is assessed through relevant financial ratios and classified using the Composite Rating (PK) system in accordance with the provisions of the Financial Services Authority (OJK). The results of the study show that state-owned banks are consistently in the Very Healthy category, reflecting the ability to maintain stability, operational efficiency, and high capital adequacy. Meanwhile, National Private Banks are in the Healthy category with variations in interbank performance, especially in the more dynamic aspects of Earnings and Risk Profile. Comparatively, State-Owned Banks excel in liquidity stability and corporate governance, while Private Banks show excellence in net interest margins and credit expansion flexibility. These findings confirm that the two groups of banks have a complementary role in maintaining the resilience of the national banking system and supporting sustainable economic growth